Morfología y demografía de la germinación en lauráceas de Costa Rica - Flores, Eugenia M. (1985)
The fruit of Licaria, Nectandra, Ocotea, Persea and Phoebe (Lauraceae) is an ovoidellipsoid berry and the ellipsoid seed has a papiraceous seed coat and a broad, straight embryo. The seedling is cryptocotylar and germination is hypogcus. The percentage of germination varies between 30-80%. The seedling develops 6 to 7 squamous protophylls before its produces eophylls in groups of 3,4 of 5; it has a well developed radical system lacking root hairs. Secondary growth takes place 40 to 45 days after germination. Seedling mortality in the field reaches almost 100% due to physical (dryness, excess of humidity) and biotic factors such as competition from weeds and fungi, and herbivory.